PERAN KEPALA SEKOLAH DALAM MENINGKATKAN KINERJA GURU DI SEKOLAH MI AL-IJTIHADIYYAH - Zahirah Hamzah, Nisrina (Program Studi Manajemen Pendidikan Islam, 2025)
This study aims to analyze the role of the principal in improving teacher performance at MI Al-Ijtihadiyyah, particularly through aspects of leadership, motivation, and evaluation. The research employed a qualitative approach with a case study design, focusing on an in-depth understanding of social phenomena within the school environment. Data collection procedures included in-depth interviews with the principal and teachers, observations of teaching and managerial activities, and document analysis. Data were analyzed using Miles and Huberman’s interactive model, consisting of data reduction, data display, and conclusion drawing. To ensure the validity of the findings, data credibility checks were conducted through source and technique triangulation, prolonged engagement in the field, and member checking with informants. The findings reveal that the principal plays a strategic role in creating a conducive working environment, providing motivation, and enhancing teacher competence through training, supervision, and performance evaluation. The principal’s role as a leader, supervisor, motivator, and facilitator has been proven to improve teacher motivation, strengthen collaboration, and foster the achievement of quality learning. Thus, school leadership significantly contributes to enhancing teacher professionalism and the overall quality of education.